2017
DOI: 10.1530/jme-17-0076
|View full text |Cite
|
Sign up to set email alerts
|

Sex dimorphic regulation of osteoprogenitor progesterone in bone stromal cells

Abstract: Augmenting peak bone mass is a promising strategy to prevent osteoporosis. A mouse model of global progesterone receptor (PR) ablation showed increased bone mass through a sex-dependent mechanism. Cre-Lox recombination was used to generate a mouse model of osteoprogenitor specific PR inactivation, which recapitulated the high bone mass phenotype. In this work, we employed RNA sequencing analysis to evaluate sex-independent and sex-dependent differences in gene transcription of osteoprogenitors of wild type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…We and others have found PR expressed in growth plate chondrocytes, osteoclasts, and osteoblasts, and PR plays a critical role in peak bone mass determination [37, 71,72]. We also have reported that the loss of PR signaling in osteoprogenitor cells regulates key signaling pathways for immune response, especially in males [34].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…We and others have found PR expressed in growth plate chondrocytes, osteoclasts, and osteoblasts, and PR plays a critical role in peak bone mass determination [37, 71,72]. We also have reported that the loss of PR signaling in osteoprogenitor cells regulates key signaling pathways for immune response, especially in males [34].…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, conditional PR deletion in the Prx1 + osteoprogenitor cells significantly suppressed immunomodulatory pathways, especially in the males. The disease pathway analyses from our previous RNA-Seq study suggested that rheumatoid arthritis is a most-likely targeted disease for PR [34]. which prompted further evaluation of the role of PR in the pathogenesis of RA in this current study.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations